2020
DOI: 10.2166/aqua.2020.051
|View full text |Cite
|
Sign up to set email alerts
|

On the transient flow behavior in pressurized plastic pipe-based water supply systems

Abstract: Plastic material pipes such as high- or low-density polyethylene (HDPE or LDPE) are increasingly used in new or renewed water supply systems. Therefore, analysis of water hammer surge-waves initiated into such piping systems deserves investigation. The 1-D pressurized-pipe flow model embedding the Ramos formulation was used to describe the flow behavior in the elastic and plastic pipe-based hydraulic system. Numerical computations were performed using the method of characteristics. First, the numerical solver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Mitosek & Szymkiewicz (2012) found that the transient flow model with the diffusive term, which represents the friction generated by compression or expansion of the fluid, could reproduce the irreversible processes at the pressure wavefront. In elastic pipes, a similar attenuation of the pressure wave magnitude was observed and was attributed to the radial compression or expansion of the pipe wall (Chahardah-Cherik et al 2021;Essaidi & Triki 2021).…”
Section: Introductionmentioning
confidence: 73%
“…Mitosek & Szymkiewicz (2012) found that the transient flow model with the diffusive term, which represents the friction generated by compression or expansion of the fluid, could reproduce the irreversible processes at the pressure wavefront. In elastic pipes, a similar attenuation of the pressure wave magnitude was observed and was attributed to the radial compression or expansion of the pipe wall (Chahardah-Cherik et al 2021;Essaidi & Triki 2021).…”
Section: Introductionmentioning
confidence: 73%
“…Hydraulic transients caused by pump failure or valve rapid closure could induce pressure surges in pipeline systems (Essaidi & Triki 2021). When the pressure drops to the saturated vapor pressure of pure liquid, vaporization would happen in the pipeline.…”
Section: Introductionmentioning
confidence: 99%